Environmental and socio-economic Pareto-front trade-off analysis of U.S. PET packaging material in a circular economy - Utkarsh S. Chaudhari; David W. Watkins; Robert M. Handler; Barbara K. Reck; Anne T. Johnson; Tasmin Hossain; Damon S. Hartley; Vicki S. Thompson; David R. Shonnard (Sustainable Production and Consumption, 2025)

Technical feasibility, technoeconomic, and life cycle assessment of CO2 sequestration using domestic nickel mine tailings: A direct ex-situ hydrothermal approach - Kobina Akyea Ofori; William Hanson; Kaiwu Huang; Vida Amankwaa; Robert Handler; Darby Stacey; Lei Pan (Journal of Cleaner Production, 2025)

Environmental life cycle analysis of manufacturing options for humanitarian supplies: drinking water containers - Robert M. Handler; Riya Roy; Joshua M. Pearce (Clean Technologies and Environmental Policy, 2025)

The methodology and results of using life cycle assessment to measure and reduce the greenhouse gas emissions footprint of “Major Events” at the University of Arizona - Leah Edwards; Jake Knight; Robert Handler; Joseph Abraham; Paul Blowers (The International Journal of Life Cycle Assessment, 2016)

Opportunities and Challenges in the Design and Analysis of Biomass Supply Chains - Pasi T. Lautala; Michael R. Hilliard; Erin Webb; Ingrid Busch; J. Richard Hess; Mohammad S. Roni; Jorge Hilbert; Robert M. Handler; Roger Bittencourt; Amir Valente; Tuuli Laitinen (Environmental Management, 2015)

A Review of Environmental Life Cycle Assessments of Liquid Transportation Biofuels in the Pan American Region - David R. Shonnard; Bethany Klemetsrud; Julio Sacramento-Rivero; Freddy Navarro-Pineda; Jorge Hilbert; Robert Handler; Nydia Suppen; Richard P. Donovan (Environmental Management, 2015)

40 Ar/ 39 Ar ages of blueschist facies pelitic schists from Qingshuigou in the Northern Qilian Mountains, western China - Yong‐Jiang Liu; Franz Neubauer; Johann Genser; Akira Takasu; Xiao‐Hong Ge; Robert Handler (Island Arc, 2006)
Pelitic schists from Qingshuigou in the Northern Qilian Mountains of China contain mainly glaucophane, garnet, white mica, clinozoisite, chlorite and piemontite. Isotopic age dating of these schists provides new constraints on the formation of the high‐grade blueschists at Qingshuigou. White mica 40 Ar/ 39 Ar ages range from 442.1 to 447.5 Ma (total fusion age of single grain) and from 445.7 to 453.9 Ma (integrated age of white mica concentrates). These ages (442.1–453.9 Ma) represent the peak metamorphic ages or cooling ages of the blueschists during exhumation shortly after peak metamorphism. The 40 Ar/ 39 Ar dates in the present study are similar to ages previously reported for eclogites and blueschists in the area; this suggests that both the eclogites and pelitic sediments underwent high‐grade metamorphism during the same subduction event. From this chronological evidence and the presence of well‐developed Silurian remnant‐sea flysch and Devonian molasse, it is concluded that the Northern Qilian Ocean had closed by the end of the Ordovician, and rapid orogenic uplift followed in the Devonian.

Post-collisional rapid exhumation and erosion during continental sedimentation: the example of the late Variscan Salvan-Dornaz basin (Western Alps) - Nicola Capuzzo; Robert Handler; Franz Neubauer; Andreas Wetzel (International Journal of Earth Sciences, 2003)